RETRACTED: Clinical Significance, Cellular Function, and Potential Molecular Pathways of CCT7 in Endometrial Cancer - Wang, Liwen; Zhou, Wei; Li, Hui; Yang, Hui; Shan, Nianchun (Frontiers in Oncology, 2020)
Objective: Endometrial cancer (EC) is a common gynecologic malignancy; myometrial invasion (MI) is a typical approach of EC spreads and an important index to assess tumor metastasis and outcome of EC patients. CCT7 is a member of the TCP1 chaperone family, involved in cytoskeletal protein folding and unfolding. In this study, the role of CCT7 in EC development was investigated. Methods: Clinical data for 87 EC cases and expression of CCT7 were analyzed. CCT7 was knocked out using siRNA-CCT7 in Ishikawa and RL95-2 cells, and their function about proliferation, apoptosis and invasion were further tested. Bioinformatics methods were used to predict the potential pathways of CCT7 in EC development. Results: The rates of CCT7-positive cells in EC and adjacent normal endometrium tissues had significant difference (67.8% vs. 51.4%, p = 0.035), and the expression rate increased from low to high pathological stage (39.7% in the I/II stage, 71.4% in the III/IV stage, p = 0.029). Similar change was found in protein level. CCT7 expression differed significantly between the deep MI group (>1/2) and the superficial MI group (≤1/2) (P = 0.039). However, there were no differences with respect to age, pathological type and histological grade. CCT7 suppression induced a function-loss in in both Ishikawa and RL95-2 cells. Bioinformatics analysis demonstrated that EC patients with lower level CCT7 expression had better Overall survival (p= 0.0081). GO enrichment indicated that “RNA binding”, “Mitochondrion”, “Translation”, and “Spliceosome” were most significantly enriched potential pathways. Five hub genes, PSMA5, PSMD14, SNRPB, SNRPG and TXNL4A, were all significantly upregulated in EC and had positive correlation with CCT7. Conclusions: CCT7 may be involved in EC development by excessively activating tumor cell function to promote MI or distant/nodal metastasis, which may contribute to the prognosis of EC patients.